2004
DOI: 10.1902/jop.2004.75.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Electrocardiographic Abnormalities and Periodontal Disease: The Hisayama Study

Abstract: This study clearly shows the relationship between periodontitis and ECG abnormalities, which are important predictors of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 42 publications
4
30
2
1
Order By: Relevance
“…Gingival bleeding is one of the definite risk predictor/markers for periodontal dis ease progression, hence we believe that this is one of the most important positive findings noted in this study that is relevant from a clinical point of view. This observation is in agreement with various other studies, 14,24,26,29,31 however, Persson et al 27 did not agree with this observation.…”
Section: British Dental Journalsupporting
confidence: 86%
See 1 more Smart Citation
“…Gingival bleeding is one of the definite risk predictor/markers for periodontal dis ease progression, hence we believe that this is one of the most important positive findings noted in this study that is relevant from a clinical point of view. This observation is in agreement with various other studies, 14,24,26,29,31 however, Persson et al 27 did not agree with this observation.…”
Section: British Dental Journalsupporting
confidence: 86%
“…Multivariate logistic regression analysis confirmed that this parameter signifi cantly correlated with AMI when other risk factors were considered. A similar observation has been noted by many authors, 22,24,27,30,31,33 how ever few others 26,40 have reported no association between PD and CHD.…”
Section: British Dental Journalsupporting
confidence: 83%
“…Studies of prevalence of ECG changes in octogenarians, Pima Indians, and a Japanese population have suggested that the risk for ECG abnormalities increases with the severity of PD. 199,264,265 In a different Japanese cohort study, no correlation between PD and prevalence of electrocardiographic abnormalities was found. 266 Thus, the independent correlation of ECG findings with PD has not been definitively proven.…”
Section: Association Of Periodontitis With Ecg Abnormalitiesmentioning
confidence: 92%
“…1,11 It is also known that subjects with advanced CP are characterized by increased left ventricular mass (LVM). [12][13][14] However, the reason for this increase is not clear. A simple path that leads from increased arterial stiffness caused by inflammatory cytokines-induced arteriosclerosis, to a resultant increase of blood pressure and at the end to increased LVM, is not confirmed.…”
mentioning
confidence: 99%